Clinical obstetrics the fetus & mother - Reece, E. Albert; Leguizamón, Gustavo F.; Macones, George A.; Wiznitzer, Arnon (Wolters Kluwer, 2022)
"From preconception care through all aspects of care of the pregnant mother and newborn infant, Clinical Obstetrics provides comprehensive, authoritative information on today's obstetrics and maternal-fetal medicine. The fourth edition has been streamlined with concise chapters summarizing clinical content for busy practitioners. The eBook provides expanded content and exciting new animations and interactive decision-making algorithms. Together, the print and eBook offer residents, trainees, and all obstetrics and maternal-fetal practitioners a comprehensive resource featuring the most up-to-date guidelines, decision algorithms, and evidence for clinical practice. Expanded with a global perspective with international co-editors and contributions from global experts in all areas of obstetrics and maternal-fetal medicine, including embryology, fetal biology, genetics, prenatal diagnosis and imaging, maternal and fetal infections and diseases, and teratology. Contains clinical management algorithms and tables for quick reference and more than 1,000 full-color illustrations that highlight diagnostic features and treatment procedures. Features a new, compact, and streamlined format in the print version for easy access; the eBook will be updated periodically with vital new studies and techniques and includes expanded text, as well as animations and interactive content. Includes 14 new chapters covering topics such as fetal surgical interventions, obesity in pregnancy, health disparities in obstetrics, thrombophilias, neonatal alloimmune thrombocytopenia, invasive diagnostic procedures, the fourth trimester, and more"--